Win some, lose some: Mesocosm communities maintain community productivity despite lower phosphorus availability because of increased species diversity. Issue 3 (22nd July 2021) - DeCock, Eva; De Schrijver, An; Schelfhout, Stephanie; Wasof, Safaa; Vanhellemont, Margot; Moeneclaey, Iris; Mertens, Jan; Verheyen, Kris; Baeten, Lander
Abstract: Aims: The restoration of degraded ecosystems typically focuses on establishing assemblages of target species, but successful recovery should also be evaluated by the ecosystem's functioning to guarantee long‐term persistence. We investigated how the processes underlying community assembly (i.e. species loss, species gain and changes in abundance of resident species) influenced ecosystem functioning in experimental grassland communities in different states of restoration. Location: A greenhouse experiment in northern Flanders, Belgium. Methods: We set up a mesocosm experiment with communities of 19 planted species, ranging from slow‐growing species from poorly productive Nardus grasslands to fast‐growing species from highly productive Lolium perenne grasslands. We categorised the mesocosms into different grassland restoration states based on known abiotic and biotic restoration barriers for semi‐natural grassland restoration: soil phosphorus levels and soil biota communities. After two growing seasons, we used the CAFE approach, an ecological application of the Price equation, to partition the effects of plant community assembly on ecosystem functioning (here community productivity) for the different restoration states. Results: Adding soil biota communities sampled from reference Nardus grasslands vs more intensively managed grasslands did not have a significant effect on either plant species richness or biomass productivity. Lower soil phosphorus concentrations (i.e. abiotic restoration) resulted in a higher plant species richness. However, the net effect on productivity was close to zero. The increase in productivity caused by species gains was compensated through decreases in productivity caused by species loss and by decreases in the abundance or functioning of species that are present in both abiotically degraded and abiotically restored states. Conclusions: Not only species richness but also species identity resulted in changes in ecosystem functioning (i.e. productivity), even though the net functional effects were close to zero. More specifically, we found that species richness‐driven increases in productivity were counterbalanced by resource‐driven and species identity‐driven reductions in productivity. Abstract : Community assembly and its effect on biomass productivity were studied by applying the Price equation on mesocosms with grassland communities in different restoration states. Restoring soil biota communities had no effect on species richness or productivity. Restoring soil phosphorus levels resulted in species increase. Species richness‐driven increases in productivity were counterbalanced by resource‐driven and species identity‐driven reductions in productivity.